PEMANFAATAN AIR TAPE KETAN PUTIH SEBAGAI KOAGULAN LATEKS KARET ALAM - Mila Lukmana (Agrisains: Jurnal Budidaya Tanaman Perkebunan Politeknik Hasnur, 2020)
Clumping is one of the important stages in the processing of latex. This stage is the first step to produce a coagulum. The purpose of this study was to determine the potential of white sticky water tape as a latex coagulant and determine the effect of white sticky water tape on the speed of clumping, color, pH, texture, levels of latex dry rubber. Tests were carried out in 4 treatments, namely R0: 1 ml of 10% formic acid solution added to 100 ml of latex; R1: 1 ml of water tape is added in 100 ml of latex; R2: 5 ml of water tape is added in 100 ml of latex; R3: Water tape as much as 10 ml was added to 100 ml of latex Then the latex parameters were observed including clumping speed, pH, texture, color and levels of dry rubber (KKK). The results of this study indicate that the administration of white sticky tape water does not reduce the pH of the latex to the isoelectric point 4.7. Nevertheless latex clumping still occurs. This is thought to be due to the alcohol content in the white sticky water tape. Based on observations, the R2 treatment is the best treatment that produces a slippery and hard coagulant texture similar to the R0 (formic acid) treatment. Whereas the latex texture in R1 and R3 treatments is softer. The addition of white sticky tape water coagulant produces latex color to milky white while formic acid produces white-yellowish color. The R2 treatment had an average KKK 41.63% lower than using formic acid, which was R0 45.96%. Although the white sticky tape water coagulant has not been able to meet the KKK quality standards of 20%.